The role of the photo novella in examining cultural competency in perioperative settings - Michael, Rene; Della, Phillip; Banner, Clare; Duckworth, Sarah; Nilson, Tor (Cambridge Publishing, 2012)
One of the major ways in which we understand the world is through vision and increasingly our everyday world is dominated by visual technology. In research this is predominately found in reports and publications in the form of the visual elements of the analyses. One visual method that is under-reported in nursing research is the use of photography, in which photographs are taken by project participants as a means of creating discussion or narratives about situations. To illustrate this approach, a snapshot of a pilot project’s preliminary findings is provided where the visual method photo novella was utilised with nursing students during their perioperative experience in a developing country. The aim was to examine the effects of a study abroad programme from the perspective of the students’ cultural competence and professional and personal development. Visual methodology is introduced, as well as the photo novella approach. The project is offered asan example to enable perioperative nurses to consider visual methodology as an alternative approach to gather information for educational, clinical or management purposes.